HPLC and ToF‒SIMS Analyses of Toxicodendron Vernicifluum Tree Sap Mixed with Other Natural Lacquers - Hye Hyun Yu (Molecules, 2021)
Lacquer sap has been used by humans from antiquitywhen it was treated as a luxury item because of its desirable physical properties. In modern times, although access barriers are lower, lacquer is still considered to be rare and valuable. Thus, low quality, inexpensive Vietnamese and Myanmarese lacquers and cashew nutshell liquid are frequently added to the costly Toxicodendron vernicifluum lacquer sap from Korea, China, and Japan. However, these blended lacquers can diminish the quality of artisan works. The Toxicodendron vernicifluum lacquer saps mixed with other natural lacquers were characterized using time-of-flight secondary-ion mass spectrometry (ToF−SIMS) and high-performance liquid chromatography (HPLC). ToF-SIMS provided the chemical structure of the lacquer monomer, copolymerized dimers, trimers, etc. HPLC provided quantitative analysis of the components of a randomly mixed lacquer. These techniques can be used to control the quality of commercial lacquer sap for the Asian lacquer industry and the traditional conservation of ancient objects.